Simulation of closed loop control of buckling of columns with piezoelectric actuators - Remanan, Mini; Srinivasan, V.; Rao, C. Lakshmana (Journal of Structural Engineering, 2024)
Analytical simulation of closed loop control of buckling of pinned columns with centrally placed piezoelectric actuators has been carried out. Basic differential equations were derived and solved to examine the effect of force generated by Lead Zirconate Titanate (PZT) actuators, on the enhancement of buckling load of a column structure. A simple proportional control strategy is adopted for the closed loop control simulation. The load defl ection plots of the column specimen are obtained using the proposed analytical procedure. The closed loop simulation demonstrates that the application of voltages to the PZT patch can enhance the buckling load of the column.